O-121 Uncovering the value of day 7 blastocysts using artificial intelligence on time lapse videos. (30th June 2022) - Innocenti, F; Cimadomo, D; Soscia, D; Casciani, V; Trio, S; Chiappetta, V; Albricci, L; Maggiulli, R; Fabozzi, G; Erlich, I; Ben-Meir, A; Har-Vardi, I; et al.
Abstract: Study question: Which is the clinical value of day 7 blastocysts? Summary answer: Ending embryo culture at 144 hours-post-insemination (hpi) would involve7.3%- and 4.4%-relative reductions in the patients obtaining euploid blastocysts and live birth(s)(LBs), respectively. What is known already: Many studies showed that day 7 blastocysts are clinically valuable although less euploid and less competent than faster growing embryos. Nevertheless, a large variability exists in: (i) the definition of "day 7"; (ii) the criteria to culture embryos to day 7; (iii)the clinical setting; (iv) the local regulation; and/or (v) the culture strategies and incubators. Here, we aimed at ironing out these differences and portray day 7 blastocysts with the lowest possible risk of bias. To this end, we have also adopted an artificial intelligence (AI)-powered software to automatize developmental timings annotations and standardize embryo morphological assessment. Study design, size, duration: Observational study including 1966 blastocysts obtained from 681 patients cultured in a time lapse incubator between January 2013 and December 2020 at a private Italian IVF center. Participants/materials, setting, methods: Trophectoderm biopsy without hatching and comprehensive-chromosome-testing were performed. Blastocysts were clustered in six groups based on the time-of-biopsy every 12hr from <120hpi (control) to > 168hpi. Blastocyst quality, time-of-expanding-blastocyst (tEB) and duration of expansion were annotated through AI and confirmed manually. The main outcomes were euploidy-rate and LB-rate (LBR) per transfer. Lastly, patients obtaining (euploid) blastocysts, LBs, and supernumerary blastocysts, were reported based on a hypothetical 144hpi cut-off, and all relative reductions calculated. Main results and the role of chance: 14.6% of the blastocysts reached full expansionbeyond 144hpi (5.9% between 144-156hpi, 7.9% between 156-168hpi, and 0.8% >168hpi). Slower blastocysts were of a worse quality based on the evaluation of both embryologists and AI. Both longer tEB and a longer duration of expansion concurred to day7 development, quite independently of embryo quality. The lower euploidy rate among day7 blastocysts is due to their worse morphology and more advanced oocyte age, rather than to a slower development per se. Conversely, the lower LBR was significant even after adjusting for confounders, with a first relevant decrease for blastocysts biopsied in the range 132-144hpi (N = 76/208, 36.5% versus N = 114/215, 53.0% in the control, multivariate-OR: 0.61, 95%CI 0.40-0.92, adjusted-p=0.02), and a second step for blastocysts biopsied in the range 156-168hpi (N = 3/21, 14.3%, multivariate-OR:0.24, 95%CI 0.07-0.88, adjusted-p=0.03). Nevertheless, when the cut-off was set at 144hpi, no significant difference was reported. In this patient population, ending embryo culture at 144hpi would have caused 10.6%-, 7.3%-, 4.4%-, 13.7%-, and 5.2%-relative reductions in the number ofpatients obtaining blastocysts, euploid blastocysts, LBs, supernumerary blastocysts without a LB and after a LB, respectively. Limitations, reasons for caution: Gestational and perinatal outcomes were not assessed, and a cost-effectiveness analysis was not performed. We encourage the production of these data in other clinical settings and regulatory contexts. Wider implications of the findings: Day7 culture shall be supported following a careful case-by-case evaluation. Patients shall be aware of their lower competence, yet day7 blastocysts are valuable for poor-prognosis couples, couples less compliant towards other attempts in case of failures, and couples wishing for second children. AI may improve the generalizability of these evidence. Trial registration number: Not applicable